Synthesis and characterization of cellulose-based aerogel and film - Ain Nadirah, Romainor (Universiti Malaysia Sarawak (UNIMAS), 2014)
Cellulose is a natural polymer which strongly meets the requirement to become one of the economical and environmental friendly precursor materials owing to its high availability, biodegradability and low toxicity. Interestingly, cellulose also can be regenerated in various forms as such fibres, films and aerogels depending on their desired applications. In this study, porous cellulose-based aerogel absorbent for oil absorption was developed. Aerogel’s allow and retain more absorbed-oil inside the pores because its offer a high surface area of porous structure. Cellulose aerogel derived from 1% (w/v) cellulose concentration was used to form coating with a layer of titanium dioxide (TiO2) to render them with hydrophobic and oleophilic properties. Magnetic nanoparticles were incorporated to impart magnetic property. The resulting magnetic cellulose/TiO2 aerogel absorbent was shown to absorb oil up to about 28 times their original weight. Instead of aerogels, this study also has regenerated cellulose in to film in order to develop cellulose antimicrobial film. Cellulose alone is lack of antimicrobial property. Therefore, antimicrobial agent such as chitosan nanoparticles was incorporated into the cellulose film to give them antimicrobial property. Influences of chitosan size-related property (nanoparticles and bulky), doping amount and citric acid crosslinking on cellulose antimicrobial film against Escherichia coli (E.coli) activity were investigated via diffusion assay, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) test. The effect of water permeability on the antimicrobial cellulose film was evaluated through the percentage of water absorbed onto the film. Based on the results obtained, a maximum of E.coli inhibition of 85% was achieved with only 5% iv (v/v) doping of chitosan nanoparticles into cellulose films. Crosslinking with citric acid has shown to reduce the water permeability of the cellulose antimicrobial film by 50%.